2023
DOI: 10.3390/jcm12051806
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automation in IVF: Pre-Clinical Validation of a Deep Learning-Based Embryo Grading System during PGT-A Cycles

Abstract: Preimplantation genetic testing for aneuploidies (PGT-A) is arguably the most effective embryo selection strategy. Nevertheless, it requires greater workload, costs, and expertise. Therefore, a quest towards user-friendly, non-invasive strategies is ongoing. Although insufficient to replace PGT-A, embryo morphological evaluation is significantly associated with embryonic competence, but scarcely reproducible. Recently, artificial intelligence-powered analyses have been proposed to objectify and automate image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…In contrast, notable differences in KIDScore and Gardner criteria were evident primarily among younger patients. Another study reported AUCs of 0.60 for iDAScore in predicting euploidy, comparable to embryologists' performance [23]. In our investigation, the combined AUC for euploidy prediction incorporating iDAScore and clinical/embryonic factors reached 0.688.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, notable differences in KIDScore and Gardner criteria were evident primarily among younger patients. Another study reported AUCs of 0.60 for iDAScore in predicting euploidy, comparable to embryologists' performance [23]. In our investigation, the combined AUC for euploidy prediction incorporating iDAScore and clinical/embryonic factors reached 0.688.…”
Section: Discussionsupporting
confidence: 74%
“…Morphological assessments have been widely used to increase the odds of selecting highest quality embryos for transfer, but are subjective and can have other limitations. Recent efforts have attempted to improve morphological assessment using artificial intelligence (AI) to increase objectivity and reproducibility in embryos (Cimadomo et al, 2023). These methods show promising associations with euploidy, but require further development, which could be facilitated by the availability of training data for less favorable embryo morphologies (Cimadomo et al, 2023).…”
Section: Noninvasive Methodsmentioning
confidence: 99%
“…Recent efforts have attempted to improve morphological assessment using artificial intelligence (AI) to increase objectivity and reproducibility in embryos (Cimadomo et al, 2023). These methods show promising associations with euploidy, but require further development, which could be facilitated by the availability of training data for less favorable embryo morphologies (Cimadomo et al, 2023). Higher accuracy may be achieved with AI coupled to time-lapse video to identify euploid blastocysts, and the use of static images combined with time-lapse video data and AI combined with other data can improve accuracy to above 80% (Salih et al, 2023).…”
Section: Noninvasive Methodsmentioning
confidence: 99%
“…All the mentioned references are depicted in Figure 1. Machine learning models are listed in Table 1 [6,7,10,17,18,[27][28][29][31][32][33][34][35][36][37], while those corresponding to the deep learning subset can be found in Table 2 [8,9,[11][12][13][14][15][16][19][20][21][22][23][24]26,[38][39][40][41][42][43]. In these tables, the AI models are described with their sample size, results and limitations.…”
Section: Artificial Intelligence In Assisted Reproductive Technologymentioning
confidence: 99%